Sustained hole inversion layer in a wide-bandgap metal-oxide semiconductor with enhanced tunnel current - Gem Shoute (Nature Portfolio, 2016)
Wide-bandgap, metal-oxide thin-film transistors are limited in their application by the lack of available p-type material. Here, the authors demonstrate a wide-bandgap metal-oxide n-type semiconductor that sustains a strong p-type inversion layer using a barrier dielectric with a high-dielectric constant.